Recombinant erythropoietin in the treatment of anemia in cancer patients - S. V. Vorobiova; T. Z. Cherniavskaya; S. G. Pushkareva; G. P. Frolov; K. N. Melkova (Онкогематология)
This article reviews the role of recombinant erythropoietin in the management of anemia in cancer patients based on literature data and our experience. We describe the problem of toxicity and report clinical recommendations and cautions for usage of drugs appertain to this pharmaceutical group.